FOLK GAMES-AN IMPORTANT FACTOR IN THE UPBRINGING OF THE PERFECT GENERATION (American Journal of Research in Humanities and Social Sciences, 2023)
The article examines the origin factors and types of national folk games and talks about their importance in raising a healthy generation. Pedagogical recommendations are given regarding the use of folk games in educational processes.